Management of foreign body aspiration or ingestion in dentistry - Parolia, A; Kamath, M; Kundubala, M; Manuel, TS; Mohan, M (Kathmandu University Medical Journal, 2010)
Foreign body aspiration or ingestion can be a potential complication during routine dental treatment. The handling of dental objects requires particular care, especially where the patient is supine or semi-recumbent. Dentist must be able to manage emergency situations in which patients accidentally swallow dental instruments or materials during treatment and procedures. This article reviews the complications, management and prevention of aspiration or ingestion of foreign bodies. Key words: Foreign bodies; Aspiration/ Ingestion; Management; Prevention DOI: 10.3126/kumj.v7i2.2715 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 165-171